Tunable stochastic resonance based on the optimization of centrifugal distance for rotation-induced energy harvesting. (1st December 2022) - Zhang, Yunshun; Zhao, Xiangshuai; Wang, Xin; Wang, Wanshu; Jia, Yu; Zheng, Rengchen
Abstract: Energy harvesting from rotating systems has been developed into an important topic as a promising solution for realizing the powering applications of tire monitoring systems. Because of relatively narrow bandwidth of the efficiently operating response, this paper proposes a principle for optimizing the centrifugal distance for tuning frequency matching between stochastic resonance and the external rotation environments. It can minimize the negative effect of a low energy orbit owing to the optimally stabilized stochastic resonance, particularly over the low frequency range before high energy orbit oscillation. The centrifugal force caused by the behavior of rotation acting on the tip mass of the cantilever changes the equivalent stiffness of the cantilever and thus can tune the variation in the Kramers escape rate. Through the match-able relationship of a non-linear bitable system between the Kramers rate and the external rotation frequency, the expression of the optimally centrifugal distance can be solved by theoretical derivation and numerical analysis. The results of simulations and laboratory experiments simultaneously demonstrate that the centrifugal distance is tuned to be the optimal 6.45 cm as theoretically analyzed, and the effective bandwidth of energy harvesting can be stabilized from 30 rad s −1 to 50 rad s −1 . While its maximum root mean square voltage can reach the value of 1.23 V corresponding to a harvesting average power of 45.55 μ W, owing to the high matching relationship between stochastic resonance and external rotation frequencies. Thus, by the theoretical optimization of centrifugal distance, the frequency of stochastic resonance can be tuned for matching the externally rotating environments, and further improving the operating performance of rotating-induced energy harvesting.